2018
DOI: 10.3389/fmed.2018.00254
|View full text |Cite
|
Sign up to set email alerts
|

Neuraxial Anesthesia in the Geriatric Patient

Abstract: Neuraxial anesthesia is recommended as a well-accepted option to minimize the perioperative side effects in the geriatric patients. The available data from the current researches have shifted the focus from the conventional approach to spinal anesthesia to the concept of low dose local anesthetic combined with opioids. What remains clear from all these studies is that hemodynamic stability is much better in patients who received low-doses of intrathecal bupivacaine in combination with opioids, which is possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Since then opioids have become the most popular adjuvants for intrathecal anaesthetic administration (8) and are widely used as a single dose to provide post-operative analgesia (4). The bene cial analgesic effects of ITM administration have become well recognised (9)(10)(11)(12)(13)(14)(15) and is considered by some to be the gold standard for single-dose neuraxial opioid due to its postoperative analgesic e cacy and prolonged duration of action (16). ITM provides decreased pain intensity and for 24 hours post-operatively with decreased adjuvant analgesic requirements, being particularly evident after abdominal surgery (17).…”
Section: Discussionmentioning
confidence: 99%
“…Since then opioids have become the most popular adjuvants for intrathecal anaesthetic administration (8) and are widely used as a single dose to provide post-operative analgesia (4). The bene cial analgesic effects of ITM administration have become well recognised (9)(10)(11)(12)(13)(14)(15) and is considered by some to be the gold standard for single-dose neuraxial opioid due to its postoperative analgesic e cacy and prolonged duration of action (16). ITM provides decreased pain intensity and for 24 hours post-operatively with decreased adjuvant analgesic requirements, being particularly evident after abdominal surgery (17).…”
Section: Discussionmentioning
confidence: 99%
“…A lower dose of local anesthetic (LA) with adjuvants such as opioids, α2-agonist, NMDA receptor antagonist reduces the chances of cardiovascular complications. [ 9 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Literature review revealed the efficacy and reduced postoperative side effects of low-dose neuraxial anesthesia in geriatric patients undergoing gynecological surgeries. [ 34 ] A smoother and quicker recovery is achieved by maintaining intraoperative euthermia, euglycemia, and euvolemia as well as avoiding or early removal of tubes and drains. The overall effect is reduced postoperative pain and opioid use.…”
Section: Oncept Of E Nhanced R Ecovery a Fter S Urgerymentioning
confidence: 99%